Bone marrow fibrosis – the basis of mielofibrosis: pathogenesis, prognostication and antifibrogenic targeted strategies. - A. S. Timchenko; V. N. Zalessky (Medičnì Perspektivi)
Bone marrow fibrosis is a key patological feature and major diagnostic criterion of mielofibrosis. Although bone marrow fibrosis is manifested in a variety of malignant  and non-malignant disease states, the deposition of reticulin and collagen fibrosis in the bone marrow of patients with myelofibrosis is believed to be mediated by the mielofibrosis of hematopoietic stem/progenitor cells, contributing to an impaired microenvironment toward malignant over normal hematopoiesis. The increased expression of proinflammatory cytokines, transforming growth factor-β, impaired megakaryocyte function and aberrant JAK-STAT signaling are the peculiarities of pathogenesis of bone marrow fibrosis. Hematopoietic stem cell transplantation remains the only therapeutic approach that reliably results in resolution of  bone marrow fibrosis in patients with mielofibrosis. In the work we review the pathogenesis, biological consequences and prognostic results of impact of bone marrow fibrosis. We discuss the rationale of various anti-fibrogenic treatment strategies targeting at clonal hematopoietic stem/progenitor cells, aberrant signaling pathway, fibrogenic cytokines, and tumor microenvironment.